HARMONIZATION OF INTERNATIONAL TRADE THROUGH “Contracts for the International Sale of Goods” - Fahmi Idris (Jurnal Justiciabelen, 2025)
The era of globalization is part of human products in this case the development of human reasoning to deal with the times, in the era of globalization digitalization is inseparable from human life, many electronic goods are sophisticated and used to help make ends meet. International sale and purchase is one of the benefits of digitization which is able to reach various countries so that a rule appears that regulates international buying and selling and is mutually agreed upon by countries, namely Contracts for the International Sale of Goods.